The time and timing costs of market work, and their implications for retirement - Daniel S. Hamermesh (Institute for the Study of Labor (IZA), 2006)
Retirement ages among older Americans have only recently begun to increase after a precipitous fifty-year decline. Early retirement may result from incentives provided by retirement systems; but it may also result from the rigidities imposed by market work schedules. Using the American Time Use Survey of 2003 and 2004, I first examine whether additional market work is neutral with respect to the mix of non-market activities. The estimates indicate that there are fixed time costs of remaining in the labor market that alter the pattern of non-market activities, reducing leisure time and mostly increasing time devoted to household production. Market work also alters the timing of a fixed amount of non-market activities during the day, away from the schedule chosen when timing constraints imposed by market work do not exist. All of these effects are mitigated by higher family income, presumably because higher-income people can purchase market substitutes that enable them to overcome the fixed time costs of market work.
Keywords: J22; D13; J26; 330; household production; non-market activity; labor-force behavior